Time reversal method with stabilizing boundary conditions for Photoacoustic tomography. (3rd November 2016) - Chervova, Olga; Oksanen, Lauri
Abstract: We study an inverse initial source problem that models photoacoustic tomography measurements with array detectors, and introduce a method that can be viewed as a modification of the so called back and forth nudging method. We show that the method converges at an exponential rate under a natural visibility condition, with data given only on a part of the boundary of the domain of wave propagation. In this paper we consider the case of noiseless measurements.